Effect of foliar spray with silicon, salicylic acid and cycocel on cucumber salt tolerance and fruit characteristics under green- house conditions - Mansour, Rama Gehad; Suleiman, Sawsan; Daies, Maher (Journal of agricultural, environmental and veterinary sciences, 2022)
The effect of foliar spray with cycocel, Salicylic acid, and Silicon on cucumber fruit characteristics, and salt tolerance under greenhouse conditions, was studied, at research center of Al- Hennadi, related to Agriculture research center – Lattakia- Syria . The research concluded 14 treatments : 1-C , 2- SA 25, 3- SA50 , 4- CCC400 , 5-CCC600, 6-Si 100 , 7- Si 200, 8-S, 9 –S+SA25 , 10- S+SA50, 11-S+ CCC400 , 12- S+ CCC600, 13- S+ Si 100, 14- S+ Si 200.The results showed that foliar spray with Si, SA and CCC improved fruit quality (dry matter, total sugars, soluble solids, total acids, and vitamin C).The results showed as well, that silicon application (Si(100,200) increased significantly the studied parameters.The results indicated that SA, CCC, and Si could alleviate the harmful effect of salinity, silicon was more effective.
Keywords: Salinity; Silicon; Salicylic acid; Cycocel; Cucumber; Green House